Circular shunt in a pulmonary artery to right atrial tunnel, an anomaly unreported so far - Anil Kumar Singhi; Kothandam Sivakumar (Wolters Kluwer Medknow Publications, 2014)
While aortico-right atrial tunnels with left to right shunt from aorta to right atrium are reported widely, pulmonary artery to right atrial tunnels have not been described so far. Such a tunnel will lead to a circular shunt with a recirculation of blood in the right sided cardiac chambers repeatedly bypassing the pulmonary capillary bed. This newly described pulmonary artery to right atrial tunnel was closed nonsurgically with a duct occluder after angiographic delineation.